The Influence of Experiential Marketing, Islamic Branding, and Word of Mouth on the Decision of New Student Enrollment at SDIT Al-Hanif Cilegon. (A Study on Parents' Perceptions) - Ani Cahyani (International Journal of Economics Accounting and Management, 2025)
In a competitive education landscape, Islamic-based schools like SDIT Al-Hanif Cilegon must adopt effective marketing strategies to attract students and parents. This study evaluates the impact of experiential marketing, Islamic branding, and Word of Mouth (WOM) on new student enrollment decisions at the school. It also explores WOM's role as a mediator between experiential marketing and Islamic branding in influencing enrollment. Data from 168 online questionnaires were analyzed using Structural Equation Modeling (SEM) via SmartPLS software. Results indicate a significant positive effect of experiential marketing on school selection (T-statistics 5.530, P-values 0.000) and a strong influence of Islamic branding on both experiential marketing (T-statistics 4.638) and WOM (T-statistics 12.004). WOM effectively mediates the relationship between experiential marketing and enrollment decisions (T-statistics 3.198, P-values 0.001). While experiential marketing through WOM shows significant influence (T-statistics 2.736, P-values 0.006), Islamic branding's impact remains suboptimal (T-statistics 1.922, P-values 0.055). Overall, the integrated marketing strategy has successfully influenced school selection decisions, meeting stakeholder expectations and achieving high parental satisfaction (88%).